Agreement between two‐ and three‐dimensional transperineal ultrasound methods for assessment of fetal head–symphysis distance in active labor. (13th January 2014) - Youssef, A.; Bellussi, F.; Montaguti, E.; Maroni, E.; Salsi, G.; Morselli‐Labate, A. M.; Paccapelo, A.; Rizzo, N.; Pilu, G.; Ghi, T.
ABSTRACT Objectives To assess the intermethod agreement between two‐dimensional (2D) and three‐dimensional (3D) transperineal ultrasound methods in measuring a new index of fetal head station (the fetal head–symphysis distance (HSD)) in active labor, and to assess potential factors that may affect their agreement. Methods HSD was measured by transperineal ultrasound in 86 women in active labor, once using a 2D and once using a 3D technique. 2D images were acquired first in 43 cases and 3D images were acquired first in the other 43 women. Intermethod agreement between 2D and 3D methods was analyzed by means of intraclass correlation coefficient (ICC) and Bland–Altman analysis. In addition, potential factors affecting the intermethod reproducibility were investigated including fetal occiput position, order of acquisition, fetal head station, stage of labor, maternal body mass index and use of epidural analgesia, using the ANOVA test to check for systematic bias and Levene's test for homoscedasticity. Results Good agreement was demonstrated between 2D and 3D measurements of HSD (ICC, 0.949 (95% CI, 0.914–0.984)). No evidence of systematic difference was shown between the two methods (average difference ± SD = 0.03 ± 2.29 mm; P = 0.888). The only factor that had a significant effect on systematic difference between 2D and 3D methods was order of acquisition (P = 0.042); the first observation was higher regardless of the method used. Fetal head station had a significant effect on the homogeneity between the two methods (P = 0.004) with a better 2D–3D agreement obtained at lower head stations (SD of differences: 1.63 vs 2.59 mm). Conclusions There is very good agreement between 2D and 3D methods of assessing HSD. Agreement is better in lower fetal head stations. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.